Mn1-xCuxO2/ reduced graphene oxide nanocomposites: Synthesis, characterization, and evaluation of visible light mediated catalytic studies. Issue 4 (15th February 2021) - Warsi, Muhammad Farooq; Bashir, Bushra; Zulfiqar, Sonia; Aadil, Muhammad; Khalid, Muhammad Usman; Agboola, Philips O.; Shakir, Imran; Yousuf, Muhammad Asif; Shahid, Muhammad
Abstract: The narrow optical band gap, higher electrical conductivity, and wider-absorption range are three key features that a good photocatalyst must possess. Herein, we have fabricated Cu-doped MnO2 (Mn1-x Cux O2 ) nanostructure by facile wet chemical approach and formed its nanocomposite with r-GO (Mn1-x Cux O2 /r-GO) via ultra-sonication approach. The successful replacement of host metal ions (Mn 4+ ) with the dopant metal ions (Cu 2+ ) was supported with the PXRD, FT-IR, and EDX characterizations. The effect of Cu-doping on the band gap and r-GO matrix on the conductivity of the fabricated nanocomposite was also evaluated via Tauc plots and I–V tests, respectively. The photocatalytic efficiency of the fabricated photocatalysts was tested and compared against the methylene blue (MB) under visible light irradiation. The photocatalytic experiments revealed that Mn1-x Cux O2 /r-GO photocatalyst exhibited superior photocatalytic aptitude than that of pristine MnO2 and Mn1-x Cux O2 photocatalysts. More precisely, the Mn1-x Cux O2 photocatalysts degraded 86.89% MB dye at the rate of 0.021 min −1 after a 90-min exposure to the visible light. Observed superior catalytic activity of the nanocomposite can be attributed to the synergistic effects between the Cu doped MnO2 and r-GO nanosheets that resulted in its narrow band-gap (2.19 eV) and excellent conductivity (2.217 × 10 −2 Scm −1 ).